A Signal Pre-processing Algorithm Applied for Ultrasonic Flow-Meter - Rang-ding Wang; Qiang Liu; Chen-tou Du; Ling Yao (Institute of Advanced Engineering and Science, 2013)
In order to solve the problem of time difference ultrasonic flow meter’s low accuracy, against the basic characteristics of the sample data, a data-processing algorithm is proposed. First, we use shell sort do a data pre-processing to the samples, then remove the error of the sample space by complex digital filter, and use the error compensation algorithm to get the final sample results. Among them, the complex digital filter is mainly composed by median filtering algorithm, sliding window, Peters algorithm and the weighted average algorithm. This kind of data processing algorithm can effectively filter out the error of the sample space. It can also make a large improvement to the accuracy of ultrasonic flow meter while ensure the stability and real-time. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3282